2018
DOI: 10.1073/pnas.1812555115
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of nucleotide release from the circadian clock protein KaiC reveal atomic-resolution functional insights

Abstract: The cyanobacterial clock proteins KaiA, KaiB, and KaiC form a powerful system to study the biophysical basis of circadian rhythms, because an in vitro mixture of the three proteins is sufficient to generate a robust ∼24-h rhythm in the phosphorylation of KaiC. The nucleotide-bound states of KaiC critically affect both KaiB binding to the N-terminal domain (CI) and the phosphotransfer reactions that (de)phosphorylate the KaiC C-terminal domain (CII). However, the nucleotide exchange pathways associated with tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 108 publications
(146 reference statements)
3
34
1
Order By: Relevance
“…Reciprocally, it is possible that KaiA pulls out the A-loop and, thereby, causes a microenvironmental rearrangement surrounding the nucleotide-binding site of the KaiC CII ring, facilitating ADP release from it. This is supported by a recently reported molecular dynamics simulation of the KaiC hexamer (Hong et al, 2018).…”
Section: Resultssupporting
confidence: 72%
“…Reciprocally, it is possible that KaiA pulls out the A-loop and, thereby, causes a microenvironmental rearrangement surrounding the nucleotide-binding site of the KaiC CII ring, facilitating ADP release from it. This is supported by a recently reported molecular dynamics simulation of the KaiC hexamer (Hong et al, 2018).…”
Section: Resultssupporting
confidence: 72%
“…(Alternatively, KaiA may pull out the tail directly.) This view supports an attractive possibility that the extension or leaping-out of the tail transmits into the inside cavity of the KaiC6mer through loop and reaches autophosphorylation and ATPase sites to promote autophosphorylation and ADP release [148,149] (see Figure 11A). (Ishii et al,unpublished [147]).…”
Section: Clock Atpasesupporting
confidence: 54%
“…KaiA binding to the CII domain (Kim et al, 2008;Pattanayek & Egli, 2015) stimulates KaiC autophosphorylation (Iwasaki et al, 2002;Williams et al, 2002;Kageyama et al, 2006). Recent work has shown that KaiA can bind to KaiC and act as a nucleotide exchange factor (Nishiwaki-Ohkawa et al, 2014) by facilitating conformational changes at the subunit interface that promote solvent exposure of the nucleotide-binding pocket (Hong et al, 2018). It is currently unclear whether this nucleotide exchange activity is responsible for all of KaiA's effect on KaiC or whether it alters the KaiC catalytic cycle in other ways (see Appendix for further analysis of this issue).…”
Section: Nucleotide Exchangementioning
confidence: 99%